The effects of acute blood flow restriction on climbing-specific tests - Saeterbakken, A. H.; Andersen, V.; Stien, N.; Pedersen, H.; Solstad, T. E. J.; Shaw, M. P.; Meslo, M.; Wergeland, A.; Vereide, V. A.; Hermans, E. (Movement & Sport Sciences - Science & Motricité, 2020)
The aim of the study was to compare climbing specific performance tests with and without blood flow restriction (BFR). Thirty one climbers (age 26.9 ± 5.5 years, height 177.2 ± 7.5 cm, weight 70.5 ± 8.3 kg, fat percentage 11.9 ± 4.1 %, climbing skill 18.9 ± 4.0 IRCRA scale) performed climbing specific grip tests measuring isometric strength (peak force, rate of force development and maximal voluntary contraction (and dynamic strength (power and peak velocity in pull-up) on a 23-mm campus rung. Further, an intermittent finger endurance (7 seconds work, 3 seconds rest at 60% of maximal voluntary contraction) test to failure was conducted. All tests were performed on two separate occasions (separated by 2-5 days) with and without blood flow restriction (200 mmHg) in a randomized order. The results demonstrated no differences in the isometric strength tests (p = 0.496-0.850, ES = 0.060-0.170), dynamic strength test (p = 0.226-0.442, ES = 0.200-0.330) or the intermittent finger endurance test (p = 0.563, ES = 0.160). In conclusion, no differences were observed in the maximal isometric pull-up test, dynamic pull-up test or finger endurance tests including measurements as peak force, MVC, RFD, power output, peak velocity or time to fatigue at 60% of MVC with and without BFR.